Uterus bioengineering as a future alternative to uterus transplantation - Arvind Manikantan Padma; Mats Brännström; Mats Hellström (IMR Press, 2022)
Objective: To review the current knowledge on uterus bioengineering and discuss potential future directives. Uterus bioengineering may solve two major hurdles in organ transplantation of a uterus, organ shortage and control of rejection by immunosuppression. Mechanism: Literature search using PubMed. Findings in brief: Sixty-seven references were summarized that describe the scientific progress made on uterus bioengineering, including other studies related to the topic. Most articles describe work on rat models, including proof-of-concept that uterus bioengineering can be used to restore fertility after a partial uterine injury. These promising results are currently being translated to larger and more clinically relevant animal models. In particular, uterus-specific scaffolds produced by a process called "decellularization" that were developed for the mouse, rat, rabbit, pig, goat, and sheep. These scaffolds stimulated angiogenesis and regeneration in vitro and in vivo, and successfully harbored various types of cells for an extended time in vitro. Additionally, applications for endometrial extracellular matrix-specific hydrogels derived from decellularized uterus tissue is discussed. Current challenges for uterus bioengineering are also addressed, e.g., the cellular reconstruction phase, and how they might be improved. Conclusions: Significant progress was made during the last decade with convincing evidence from multiple independent groups in experiments with small animal models. Initial steps towards large animal uterus bioengineering were made. The future continuation of such studies will provide important data required to translate these ideas to an experimental phase in the human. Partial uterus reconstruction through a bioengineered tissue transplantation is closer to a clinical reality compared to whole uterus bioengineering principles aimed to replace a donor in a UTx setting.